A review on fabrication of blazed gratings. (24th May 2021) - Gao, Jian; Chen, Peng; Wu, Lei; Yu, Bingjun; Qian, Linmao
Abstract: Ultra-precision manufacturing plays a critical role in the successful development of various technological fields and has a significant influence on the processes conducted in human society. Blazed gratings with periodically inclined structures exhibit satisfactory characteristics, concentrating most of the diffracted light to a single, non-zero order. In addition to their high diffraction efficiency, blazed gratings can also significantly improve the sensitivity, resolution, and measurement range of grating measurement systems; they are also core functional components for improving ultra-precision manufacturing. Significant research and industrial attention have been devoted toward the manufacturing of blazed gratings. This review describes the physical principles of blazed gratings, the specific approaches used, and the achievements of typical processing methods, including mechanical ruling, holographic ion beam etching, electron beam lithography, and wet etching. The advantages and disadvantages of these fabrication methods were addressed, and prospective approaches were proposed to improve the manufacturing of blazed gratings.